Predictive accuracy of elevated mitotic rate on lymph node positivity and recurrence in thin melanomas - Ly, Catherine L.; Blaha, Ondrej; Wei, Wei; Galan, Anjela; Kluger, Harriet; Ariyan, Stephan; Olino, Kelly; Clune, James E. (Frontiers in Oncology, 2023)
Background: Mitotic rate (MR) is considered an important prognostic factor for melanoma but is not currently used for staging because its nuanced effect is not yet well-delineated. We sought to determine if T category-specific MR is predictive of sentinel lymph node (SLN) positivity, recurrence, and melanoma-specific mortality (MSM). Methods: A retrospective review of patients with primary cutaneous melanoma from 1994 to 2020 at a single academic center was performed. Patient demographics and tumor characteristics were recorded. MR was considered elevated for each AJCC8-defined T category if it was ≥2 mitoses/mm2 for T1, ≥4 mitoses/mm2 for T2, ≥6 mitoses/mm2 for T3, or ≥7 mitoses/mm2 for T4. Statistical analysis was performed to assess the predictive accuracy of MR on selected outcomes while controlling for ulceration. Results: Data from 2,984 patients with complete records were analyzed. Along with Breslow thickness and ulceration, elevated MR was associated with higher risk of MSM (HR 1.816, P=0.0001). There was no difference among patients with ulcerated T1 or T2 tumors regardless of MR, but those with non-ulcerated T1 or T2 tumors and elevated MR were more likely to have positive SLNs (P<0.0001 and P=0.0043, respectively) and recurrence (P=0.0007 and P=0.0004, respectively) compared to counterparts with low MR. There were no notable differences for T3 or T4 tumors based on MR. Conclusions: Elevated MR is associated with SLN positivity and recurrence in thin melanomas, independent of ulceration. SLN biopsy should therefore be strongly considered for patients with non-ulcerated lesions <0.8 mm thick if the MR is ≥2 mitoses/mm2.